The Philosophical Role of Morality in Law Enforcement - Lodwyk Wessy; Yeheskel Wessy (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
Law enforcement is not merely the application of positive norms contained in statutory regulations, but also involves the dimension of morality inherent in every legal process. This study emphasizes the role of morality in law enforcement through a philosophical approach that focuses on the relationship between law, justice, and moral values. The relationship between morality and law is a central issue in the study of legal philosophy and continues to be a subject of debate among legal scholars and practitioners. Although law and morality are distinct entities, they are closely related and influence one another. Laws that do not reflect the moral values of society tend to lose their legitimacy and enforceability. Conversely, morality as the foundation for lawmaking can enhance substantive justice and foster public trust in the legal system. Therefore, understanding the link between law and morality is crucial to ensure that the law is not only formally legal but also ethically sound. This article also examines the extent to which morality influences the process of law enforcement in the context of achieving substantive justice, particularly in the decisions of law enforcement officers such as judges, prosecutors, and police. Morality plays a vital role as an ethical consideration in interpreting and applying the law fairly. However, in Indonesia, the influence of morality in law enforcement remains sporadic and highly dependent on the integrity and moral sensitivity of legal actors. Hence, integration between morality and positive law must be strengthened so that the law enforcement process can consistently and sustainably achieve substantive justice. Morality plays a crucial role in assessing the justice of legal norms and in the practices of law enforcement officials. When positive law contradicts the sense of justice and public morality, morality becomes an essential reference for assessing the legitimacy and acceptability of law enforcement. Therefore, harmonizing positive law with moral values is necessary to ensure that law enforcement is not only formally legal but also substantively just.